Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.4 Exercises - Page 352: 43



Work Step by Step

$g(t)=(e^{-t}+e^t)^3$ let u=$e^{-t}+e^t$ u'=$-e^{-t}+e^t$ $g(u)=u^3$ $g'(u)=3u^2u'$ $gā€™(t)=3(e^{-t}+e^t)^2(-e^{-t}+e^t)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.